2017
DOI: 10.4028/www.scientific.net/aef.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of HVOF Sprayed Coatings on ASME SA213 T22 Boiler Steel in an Actual Boiler Environment

Abstract: In present study HVOF spraying process had been employed for depositing 93(WC-Cr3C2)-7Ni, 75Cr3C2-25NiCr, 83WC-17CO and 86WC-10CO-4Cr coatings on ASME SA213 T22. All the coatings were found dense and uniform having thickness between 200-250µm. All the coatings on ASME SA213 T22 used in present studies have provided resistance to corrosion in coal fired boiler environment in superheater zone when exposed for 10 cycles at 900°C. Each cycle consists of 100 hours heating followed by 1 hour cooling at ambient condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The coated alloy's oxide scale spallates, as shown in BSE images (Figure 4b). Nickel and chromium oxides along with their spinels could be accountable for hindering the transference of degrading species through the applied coating [52,53]. Chromium and cobalt oxides, coupled with cobalt–chromium (CoCr 2 O 4 ) and nickel-chromium (NiCr 2 O 4 ) spinels, may have hindered CoO diffusing activities by preventing its production [28,54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coated alloy's oxide scale spallates, as shown in BSE images (Figure 4b). Nickel and chromium oxides along with their spinels could be accountable for hindering the transference of degrading species through the applied coating [52,53]. Chromium and cobalt oxides, coupled with cobalt–chromium (CoCr 2 O 4 ) and nickel-chromium (NiCr 2 O 4 ) spinels, may have hindered CoO diffusing activities by preventing its production [28,54].…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional EDAX analysis also confirms the formation of similar phases. Sidhu et al [55] and Singh et al [52] reported the presence of these phases during their investigation of appraising the hot corrosion performing of Ni-Cr coatings in coal-fired boiler environmental conditions. The cross-sectional analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otero et al (1987) had explained that Na 2 SO 4 − 60%V 2 O 5 leads to the spallation of the protective oxide scales formed on the surface of steel alloys due to which the surface comes into direct contact with the corrosive environment resulting in higher weight gain. Sidhu et al (2017) observed that steel alloys underwent extensive sputtering, spallation, peeling of scale and high weigh gain in Na2SO4-60%V2O5 environments. The high rate of weight gain was attributed to the formation of NaVO3, which acts as a catalyst and carries oxygen to the substrate causing high rate of oxidation of base elements of alloy (Rani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After testing it was found that the corrosion resistance for coated material was more than that of bare material. Cr/Co-Al coating provided the thin layer of protective oxides (Cr2O3, Al2O3 and CoCr2O4), and these protective oxides provided protection against corrosion (Sidhu et al, 2017;Xi et al, 2017;Cabral Miramontes et al, 2018;Dorfman, 2018;Dudziak et al, 2018;Goyal, 2018). It is reported in the literature that the thermal spray coatings are effective to provide the resistance against corrosion, wear, oxidation and erosion in boilers and chemical process plants components (Poursaeidi et There is scope to develop composite coatings of Cr3C2-NiCr and to deposit these coatings on boiler steel to increase its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%